PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI COFFEE BEAN & TEA LIFE TRANS STUDIO MALL CIBUBUR KOTA DEPOK - Novi Dwi Handayani; Anah Furyanah (Journal of Research and Publication Innovation, 2025)
The purpose of this research was to determine the effect of the Social Media Instagram Promotion and Brand Image on the Buying Decision at Trans Studio Mall Cibubur Kota Depok. The research method used is descriptive quantitative by using a questionnaire measuring tool. The population in this study were all visitors to Coffee Bean & Tea Life Trans Studio Mall Cibubur, Depok City. The sampling technique used is purposive sampling, which involves selecting subjects who are at the most advantageous location or in the best position to provide the required information. Testing method in this research are validity test, reliability test, classical assumption test, hypothesis testing (t-test and F-test), correlation of coefficient test, and coefficient of determination test with SPSS version 25 program. The result of the research is that the Social Media Instagram Promotion partially have a significant effect on Buying Decision. Based on the results of the partial test (t-test), the Social Media Instagram Promotion variable with a value of t-count > t-table is 5,341 > 1,984 with a significant value of 0.000 < 0.05. Brand Image partially have a significant effect on Buying Decision. Based on the result of the partial test (t-test), the Brand Image variable with a t-count value of 6,706 > t-table 1,984 with a significant value of 0.000 < 0.05. Social Media Instagram Promotion and Brand Image simultaneously have a significant effect on Buying Decision, based on the result of F-test that F-count (31,467) > F-table (3.09) and the significant value is 0.000 < 0.05. Based on the coefficient of determination test, R Square 0,394 that the contribution of the variable Brand Image and Store Atmosphere to Buying Decision is 39,4%, while the remaining 60,6% is influenced by other variables not used in this research.